Singapore's five decades of development lessons and future directions - Chia, Siow Yue ([Quezon City] School of Economics, University of the Philippines, 2015)
This paper looks at Singapore's transition from a Third World economy at the time of political independence in August 1965 to a First World economy five decades later. It is a unique city-state with a dearth of land and natural resources and pursuing a government-led, mnc (multinational corporation)- led, and export-led development strategy. Government and governance have been outstanding, and the city-state overcame its constraints by adopting open trade and investment policies, making the region and the world its economic hinterland. Five decades later, while facing the same demographic and land constraints, it has to overcome the challenges of transitioning into a private-enterprise-driven and innovation-driven economy.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 64)
Keywords: Economic development -- Singapore; Singapore -- Economic policy; Singapore -- Economic conditions